2024
DOI: 10.1044/2024_jslhr-23-00470
|View full text |Cite
|
Sign up to set email alerts
|

Age Impacts Speech-in-Noise Recognition Differently for Nonnative and Native Listeners

Ian Phillips,
Rebecca E. Bieber,
Coral Dirks
et al.

Abstract: Purpose: The purpose of this study was to explore potential differences in suprathreshold auditory function among native and nonnative speakers of English as a function of age. Method: Retrospective analyses were performed on three large data sets containing suprathreshold auditory tests completed by 5,572 participants who were self-identified native and nonnative speakers of English between the ages of 18–65 years, including a binaural tone detection t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 121 publications
1
7
0
Order By: Relevance
“…The goal of this study was to examine the impact of two aspects of bilingual language experience on English speech-in-noise recognition in a large participant cohort in order to expand on prior findings indicating an exaggerated effect of aging on speech-in-nose recognition in bilingual adults (Phillips et al, 2024). In the present study, monolingual and bilingual adults completed the MRT, a word-level measure of speech recognition in noise with accuracy and response times as the outcome measures of interest.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The goal of this study was to examine the impact of two aspects of bilingual language experience on English speech-in-noise recognition in a large participant cohort in order to expand on prior findings indicating an exaggerated effect of aging on speech-in-nose recognition in bilingual adults (Phillips et al, 2024). In the present study, monolingual and bilingual adults completed the MRT, a word-level measure of speech recognition in noise with accuracy and response times as the outcome measures of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Current Age. This study was motivated in part by prior findings documenting a stronger effect of current age on accurate recognition of low-context sentences and digit strings in self-identified non-native speakers of English as compared to their native speaker peers (Phillips et al, 2024). In that prior study, non-native speakers of English showed relatively larger age-related detriments on the speech-in-noise tasks.…”
Section: Differences Between Monolinguals and Bilingualsmentioning
confidence: 98%
See 3 more Smart Citations